Premature closure of the ductus arteriosus causing intra-uterine death. A case report - Truter, P J; Franszen, S; van der Merwe, J V; Coetzee, M J (South African medical journal, 1986)
A case of hydrops fetalis with intra-uterine death after premature closure of the ductus arteriosus because of inhibition of premature labour by the administration of indomethacin is presented. The physiology of acute and chronic intra-uterine constriction of the ductus arteriosus and the effects of indomethacin on the fetal circulation are discussed. Mention is also made of the moral conflict confronting the doctor in the management of an affected fetus during the third trimester.